Early Warning of Rejection?. Issue 5861 (5th May 1973) - Wellwood, J. M.; Ellis, B. G.; Hall, J. H.; Robinson, D. R.; Thompson, A. E.
Abstract : The urinary excretion of N-acetyl-β-D-glucosaminidase (NAG), β-galactosidase (GAL), β-glucosidase (GLU), and alkaline phosphatase (AP) was studied in 83 patients with renal allografts. Thirty of these patients had stable graft function and their urinary enzyme levels provided a range of normal values. Urinary lactic dehydrogenase (LDH) was estimated in 29 normal subjects and in 11 patients with renal allografts. Serum values for the five enzymes were also obtained. Urinary NAG excretion was abnormally high in 16 out of 17 (94%) episodes of acute rejection. The other urinary enzymes were raised less frequently. In nine patients studied before the onset of rejection urinary NAG activity rose up to three weeks before changes in other tests of renal function. Serum enzyme levels were not found to be of value in the diagnosis of rejection.